A Stylistic Analysis of Figures of Speech in Tariq Rehman’s Bingo from The Legacy and Other Short Stories - Shah, Abdul Rauf alias Wazir Ali (Pakistan Languages and Humanities Review, 2024)
The aim of this study is to analyze the role of the figures of speech by performing a stylistic analysis of Tariq Rehman’s short story Bingo from the collection The Legacy and Other Short Stories. This analysis is qualitative in nature and utilizes content analysis approach hence the result involves identifying the figures of speech used such as metaphors, similes, personification, and hyperbole among others. The author notes that Rehman succeeds in the use of figures of speech to draw attention to the psychology of characters, help in strengthening the aspects of loss and nostalgia in the themes, as well as adding to the overall vividness of the novel’s descriptions. Further research on how cultural context influence the use of the rhetorical modes that appear in Rehman’s writing can be conducted and comparison between Rehman’s work and other writers in South Asian region can also be done.